Genome-wide survey and expression analysis of Dof transcription factor family in sweetpotato shed light on their promising functions in stress tolerance - Zhang, Chengbin; Dong, Tingting; Yu, Jing; Hong, Haiting; Liu, Siyuan; Guo, Fen; Ma, Hongting; Zhang, Jianling; Zhu, Mingku; Meng, Xiaoqing (Frontiers in Plant Science, 2023)
DNA-binding with one finger (Dof) transcription factors play a crucial role in plant abiotic stress regulatory networks, although massive Dofs have been systematically characterized in plants, they have not been identified in the hexaploid crop sweetpotato. Herein, 43 IbDof genes were detected to be disproportionally dispersed across 14 of the 15 chromosomes of sweetpotato, and segmental duplications were discovered to be the major driving force for the expansion of IbDofs. The collinearity analysis of IbDofs with their related orthologs from eight plants revealed the potential evolutionary history of Dof gene family. Phylogenetic analysis displayed that IbDof proteins were assigned into nine subfamilies, and the regularity of gene structures and conserved motifs was consistent with the subgroup classification. Additionally, five chosen IbDof genes were shown to be substantially and variably induced under various abiotic conditions (salt, drought, heat, and cold), as well as hormone treatments (ABA and SA), according to their transcriptome data and qRT-PCR experiments. Consistently, the promoters of IbDofs contained a number of cis-acting elements associated with hormone and stress responses. Besides, it was noted that IbDof2 had transactivation activity in yeasts, while IbDof-11/-16/-36 did not, and protein interaction network analysis and yeast two-hybrid experiments revealed a complicated interaction connection amongst IbDofs. Collectively, these data lay a foundation for further functional explorations of IbDof genes, especially with regards to the possible application of multiple IbDof members in breeding the tolerant plants.